Localizing the sustainable development goals to accelerate implementation of the 2030 agenda for sustainable development the current state of sustainable development goal localization in Asia and the Pacific. - Oosterhof, Pytrik Dieuwke (The Governance Brief, 2018)
This brief elaborates on the concept of Sustainable Development Goal (SDG) localization and analyzes to what extent localization is considered in the implementation of the SDGs in Asia and the Pacific.This is in the wake of the growing recognition around the importance of bringing the SDGs to the local level in the context of Agenda 2030. Through the lens of policy coherence and a multilevel governance approach, the brief provides context to why and how effectively leveraging SDG localization is critical for achieving sustainable development by 2030. Drawing on the member state mechanism of Voluntary National Reviews, the governance brief looks at localization initiatives highlighted by countries in the Asia and Pacific region and considers issues in need of specific attention for effectively localizing the SDGs.